Pengaruh Kepemilikan Institusional, Umur Perusahaan, Opini Audit, Dan Ukuran Perusahaan Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan - Nur Azizah Latif; Mustakim Muchlis; Raodahtul Jannah (Academic Bright Collaboration, 2024)
This research aims to determine the influence of institutional ownership, company age, audit opinion, and company size on the timeliness of submitting financial reports in consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX). This research is quantitative research with a comparative causal approach. The data source in this research is secondary data obtained from the official IDX website and from each company's website in the form of financial reports. The population in this study are companies included in the consumer cyclicals sector listed on the IDX for the 2021-2022 period. The sampling method in this study used a purposive sampling method, with the total number of samples obtained being 210 samples. The analysis used to test the hypothesis is using logistic regression analysis with the help of SPSS version 26. The results of this research show that the audit opinion variable has a positive and significant effect on the timeliness of submitting financial reports. Meanwhile, the variables institutional ownership, company age and company size do not have a positive and significant effect on the timeliness of financial report.